Levelling the field: A review of the ICT revolution and agricultural extension in the Global South - Khan, Rashid Parvez; Gupta, Saurabh; Daum, Thomas; Birner, Regina; Ringler, Claudia (Wiley, 2025)
Information and communications technology has evolved significantly over the last seven decades, beginning with radio and video vans and culminating in the rise of smartphones and mobile internet in remote areas of the Global South. While ICT is an integral part of agricultural extension, little is known about how these changes have influenced agricultural extension practices. After a systematic review of 131 papers, we find that changes in ICT have shaped agricultural extension, enabling a shift from linear dissemination and “one-way communication” to co-innovation and farmer-to-farmer learning. The results indicate the potential for smartphones and mobile internet to democratize agricultural extension.